Smart Law Enforcement and Urban Mobility: Evaluating the Impact of Electronic Traffic Law Enforcement (ETLE) on Traffic Discipline (Kamseltibcarlantas) in Emerging Cities - Amiruddin, Suwaib; Aziz, Yugni Maulana; Rosyid, Mohamad Iyos; Danial, Dian Wahyu; Sugiharto, Agus; Nurfebriansyah, Ahmad Rifki (Journal of Cultural Analysis and Social Change, 2025)
This research discusses the Implementation of the Electronic Traffic Law Enforcement (ETLE) Program and the mechanisms and legal sanctions in order to create Kamseltibcarlantas in the Rangkasbitung City Area, Lebak Regency, Banten Province. The research method used in this study is a descriptive qualitative method. The theory used is Edward III's theory of Public Implementation seen from four variables, namely communication. Resources, disposition, and organizational structure. In the discussion of this study, it is seen from vehicle users in complying with traffic and the ETLE program whether it is carried out properly or whether there are obstacles in its implementation. The purpose of this is to achieve Security, Safety, Order, and Smooth Traffic (Kamseltibcarlantas) desired by every road user. The behavior of road users greatly influences the realization or not of Kamseltibcarlantas in the Rangkasbitung City area, Lebak Regency, Banten Province.